1992
DOI: 10.1038/eye.1992.5
|View full text |Cite
|
Sign up to set email alerts
|

Cystoid macular oedema following neodymium: YAG laser capsulotomy a prospective study

Abstract: occurs at a rate of 25% to 50%.4,5,6,7 The resulting deterio ration in visual acuity necessitates posterior capsulotomy, which is currently performed using the Neodymium: YAG (Nd:YAG) laser. Although safer and less invasive than surgical discission this procedure is nevertheless thought to be associated with numerous complications, such as increased intraocular pressure,8,9,10,11,12 corneal endothe lium damage,8,9 pitting of the intraocular lens, IO,11 retinal tears and detachment,8,9,12,13,14,15,16,17,18,19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
2
1
2
Order By: Relevance
“…In these studies, the rate of CME following Nd:YAG laser capsulotomy was reported as 0 to 5.6% [8,19,20]. In our study, there were no significant changes in macular thickness following Nd:YAG laser capsulotomy for 6 months (P [ 0.05).…”
Section: Discussioncontrasting
confidence: 39%
“…In these studies, the rate of CME following Nd:YAG laser capsulotomy was reported as 0 to 5.6% [8,19,20]. In our study, there were no significant changes in macular thickness following Nd:YAG laser capsulotomy for 6 months (P [ 0.05).…”
Section: Discussioncontrasting
confidence: 39%
“…15 It has been suggested that longer the interval between cataract surgery and capsulotomy, the smaller the risk of retinal complication. 16 Retinal detachment and cystoid macular edema may develop many months after capsulotomy therefore patients undergoing YAG laser capsulotomy require long term follow up to detect and treat these serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The avoidance of potential surgical complications such as endophthalmitis, and the shorter postoperative recovery has made the Nd: YAG laser capsulotomy a widespread and popular approach for treatment of PCO. In Nd: YAG laser posterior capsulotomy, some complications have been reported such as increased intraocular pressure (IOP), [15][16][17][18][19][20][21] cystoids macular edema, 18,[22][23][24] retinal detachment 22,[24][25][26] , endophthalmitis, 14,16,18,22,23 anterior vitreous opacification and destruction 26,27 , IOL damage and decentration, 15,18,28,29 posterior subluxation of IOL into vitreous cavity 30 and lowering of endothelial cell count of the cornea 31 , as well as macular hemorrhage. 32 Complications are infrequent but very severe, having great impact on visual acuity.…”
Section: Introductionmentioning
confidence: 99%